Teaching Austrian Economics Through Fiction: A Summary & Analysis of Time Will Run Back by Henry Hazlitt - Cesario, Anthony (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2022)
While many may be familiar with Henry Hazlitt through his non-fiction writing on Austrian economics, he also published a lesser-known and extremely underappreciated fictional story, Time Will Run Back. Despite the fact that it was the only work of fiction that he ever wrote, it is an absolute Austrian masterpiece that incorporates an extensive amount of Socratic dialogue to not only adeptly guide the reader through Mises’ economic calculation problem but also to teach many of the economic principles associated with it. The main theme of the book is that “if capitalism did not exist, it would be necessary to invent it — and its discovery would be rightly regarded as one of the great triumphs of the human mind” (Hazlitt, 1993, p. 82). This paper reviews the story from an Austrian perspective and discusses some of the creative ways that it manages to teach various economic principles referenced throughout the work.